Hollow nanorod array oxygen evolution electrode and preparation method and application thereof
The preparation of nickel-ferrous bimetallic hydroxide nanosheets coated with cobalt hydroxide hollow nanorod array oxygen evolution electrodes was solved by using continuous electrodeposition under alkaline conditions, and the problem of low oxygen evolution reaction efficiency in the electrolytic water hydrogen production process was solved, and efficient electrocatalytic performance and stability were achieved.
Patent Information
- Application Number
- CN202411741433.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-28
AI Technical Summary
In the prior art, during the process of electrolyzing water hydrogen production under alkaline conditions, the anode oxygen evolution reaction efficiency is low, which hinders the large-scale application of electrolyzed water.
The nickel-iron bimetallic hydroxide nanosheets were prepared by continuous electrodeposition method and a self-supported oxygen evolution electrode was coated with cobalt hydroxide hollow nanorod array, forming a unique three-dimensional layered structure through three electrodeposition reactions.
Under alkaline conditions, the electrocatalytic performance of oxygen evolution is significantly improved, the overpotential of the electrolytic water reaction is reduced, and the catalytic activity and stability of the electrode are improved.
Smart Images

Figure HDA0005162681610000011 
Figure HDA0005162681610000012 
Figure HDA0005162681610000021
Abstract
Description
Technical Field
[0001] The invention relates to a hollow nanorod array oxygen evolution electrode and a preparation method and application thereof, belonging to the field of hydrogen production by alkaline water electrolysis. Background Art
[0002] Hydrogen production by water electrolysis has the advantages of high catalytic efficiency, high purity of hydrogen production, and environmental friendliness, and is regarded as one of the most promising hydrogen production technologies. Hydrogen production by alkaline water electrolyzers has attracted widespread attention because it can use low-cost non-precious metal electrocatalysts to replace precious metals Ir and Ru, although its energy conversion efficiency (≈70%) needs further improvement. However, the large-scale application of water electrolysis is mainly hindered by the slow oxygen evolution reaction at the anode. Therefore, it is necessary to design and explore oxygen evolution electrodes with high catalytic activity and long life.
[0003] The core of the electrolysis process is the electrocatalyst required for the electrochemical reaction, which directly affects the electrolysis efficiency, electrolysis energy consumption, electrolysis cost and the life of the electrolytic cell. Recently, there has been a trend of increasing research on non-precious metal oxygen evolution catalysts used under alkaline conditions.
[0004] Patent CN106149025A describes a one-step electrosynthesis method for nickel-iron hydrotalcite nanosheets. Although the method is simple and fast, there is no relevant data showing that the electrode prepared by this method can obtain excellent OER performance, and the microscopic morphology of the electrode prepared by this method is difficult to control. Patent CN105618060A describes a non-metallic bifunctional oxygen catalyst of graphene / nickel-iron hydrotalcite. In actual application, the catalyst particles are difficult to arrange in order, so it is difficult to obtain a high dispersion, and the utilization rate of the catalyst is not high.
[0005] Numerous current research results show that self-supporting electrodes without binders or resins are more suitable for alkaline media than traditional binary or even ternary transition metal oxides, and can be used at higher electrolysis currents (300-1000 mA cm -2 ), and can operate stably in strong alkaline media for a long time, and is currently one of the most promising OER electrodes. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing a self-supporting electrode of a nickel-iron double hydroxide nanosheet-coated cobalt hydroxide hollow nanorod array used under alkaline conditions, so as to ensure that the self-supporting oxygen evolution electrode prepared according to the method can enable the water electrolysis reaction to proceed efficiently at a relatively small overpotential.
[0007] This method adopts a continuous electrodeposition method, and then washes and vacuum-dries to obtain a self-supporting nickel-iron double metal hydroxide nanosheet-coated cobalt hydroxide hollow nanorod array oxygen evolution electrode. This structural design in which one-dimensional nanotubes can disperse two-dimensional nanosheets ensures the order and stability of the nanostructure. Compared with the preparation method of traditional catalysts, this method has the advantages of simplicity, low cost, and easy industrial production. The morphology and structure of the synthesized catalyst can be effectively controlled under relatively mild conditions, and it has good catalytic activity and stability.
[0008] The present invention adopts the following technical solutions:
[0009] The invention provides a self-supporting three-dimensional layered hollow nanorod array composite structure - a nickel-iron double metal hydroxide nanosheet-coated cobalt hydroxide hollow nanorod array oxygen evolution electrode, wherein the electrode comprises a substrate and a catalytically active component, wherein the substrate is nickel foam, and the active components are cobalt hydroxide and nickel-iron double metal hydroxide; a hollow nanorod structure grows vertically on the surface of the nickel foam substrate, wherein the hollow nanorod structure comprises a hollow nanorod-shaped cobalt hydroxide layer located inside, and multiple layers of nickel-iron double metal hydroxide nanosheets wrapped on the surface of the hollow nanorod-shaped cobalt hydroxide layer; the hollow nanorod has a diameter of 0.2 to 1 μm and a length of 2 to 3 μm; multiple layers of nickel-iron double metal hydroxide are wrapped on the surface of the hollow nanorod to form a structure similar to a "flower branch".
[0010] In the above technical solution, further, the diameter of the hollow nanorods is 0.2 to 1 μm.
[0011] In the above technical solution, further, the electrode grows vertically on the surface of nickel foam, the thickness of the nickel foam is 0.8-1 mm, and Ni>99.9%; the weight ratio of the electrode's multi-layered nickel-iron double metal hydroxide nanosheets and cobalt hydroxide hollow nanorods is 0.995-1.005:3.995-4.005.
[0012] In the above technical solution, further, the Ni content in the nickel-iron double hydroxide is 5-10wt%; the cobalt content in the cobalt hydroxide hollow nanorods is 75-80wt%.
[0013] In the above technical scheme, a three-dimensional layered self-supporting multi-layered nickel-iron double metal hydroxide nanosheet-coated cobalt hydroxide hollow nanorod array oxygen evolution electrode is obtained under relatively mild conditions by continuous electrodeposition reaction; the catalyst active component loading per unit area on the nickel foam substrate is 0.045-0.055 g cm -2 .
[0014] In the above technical solution, the present invention further provides a method for preparing the above electrode, comprising the following steps:
[0015] (1) Preparation of ZnO nanorod array self-supporting oxygen evolution electrode by electrodeposition reaction 1:
[0016] Preparation of electrodeposition precursor solution I: Dissolve the zinc salt precursor and the weak alkaline salt precursor in a certain amount of deionized water at room temperature, and stir them in a N2 atmosphere to fully dissolve them;
[0017] Electrodeposition experiment I: A three-electrode system was used, with a graphite plate as the counter electrode, a saturated calomel electrode as the reference electrode, and nickel foam as the working electrode. Constant current deposition was performed under a N2 atmosphere. After deposition, the obtained electrode was washed with deionized water and dried to obtain a ZnO nanorod array self-supporting oxygen evolution electrode; after electrodeposition reaction 1, a ZnO nanorod array loaded on a nickel foam substrate was obtained; a nanorod array with a length of 2 to 3 μm and an average diameter of 100 to 500 nm was vertically grown on the obtained nickel foam substrate in the shape of a hexagonal prism.
[0018] (2) Preparation of cobalt hydroxide coated ZnO nanorod array self-supporting oxygen evolution electrode by electrodeposition reaction 2:
[0019] Preparation of electrodeposition precursor solution II: Dissolve the cobalt salt precursor and the complexing agent in deionized water at room temperature and stir to fully dissolve;
[0020] Electrodeposition experiment II: using a three-electrode system, with a graphite plate as the counter electrode, a saturated calomel electrode as the reference electrode, and the ZnO nanorod array self-supporting oxygen evolution electrode obtained in the above step (1) as the working electrode, after constant current deposition under N2 atmosphere; washing and drying, the cobalt hydroxide-coated ZnO nanorod array self-supporting oxygen evolution electrode is obtained;
[0021] Soaking in KOH solution to remove the ZnO template, then washing with deionized water and drying to obtain a cobalt hydroxide-coated ZnO hollow nanorod array self-supporting oxygen evolution electrode;
[0022] The electrodeposition reaction 2 obtains an oxygen evolution electrode with a cobalt hydroxide-coated ZnO nanorod array supported on a nickel foam substrate; the final morphological characteristics of the oxygen evolution electrode loaded with a cobalt hydroxide-coated ZnO nanorod array are: a hollow nanorod array with a length of 2 to 3 μm and a diameter of 200 to 500 nm on the surface of the nickel foam substrate, but the surface becomes rough.
[0023] (3) Preparation of NiFe LDHs-coated cobalt hydroxide hollow nanorod array oxygen evolution electrode by electrodeposition reaction 3:
[0024] Preparation of electrodeposition precursor solution III: stirring and dissolving the nickel salt precursor, the iron salt precursor, the buffer and the complexing agent at room temperature;
[0025] Electrodeposition experiment III: using a three-electrode system, with a graphite plate electrode as the counter electrode, a saturated calomel electrode as the reference electrode, and the cobalt hydroxide-coated ZnO nanorod array oxygen evolution electrode obtained in step (2) as the working electrode; after constant current deposition under N2 atmosphere, washing and drying; washing with deionized water and drying to obtain the self-supporting NiFe LDHs-coated cobalt hydroxide hollow nanorod array oxygen evolution electrode.
[0026] The nickel foam obtained by electrodeposition reaction 3 is loaded with a nickel-iron double metal hydroxide-coated cobalt hydroxide hollow nanorod array oxygen evolution electrode. The final morphological characteristics of the self-supporting nickel-iron double metal hydroxide-coated cuprous sulfide hollow nanorod array oxygen evolution electrode catalyst layer are as follows: each nanorod is a hollow nanorod formed by multiple layers of nickel-iron double metal hydroxide-coated cobalt hydroxide, with an average diameter of 0.2 to 1 μm and a length of 2 to 3 μm.
[0027] In the above technical solution, further, the nickel foam of step (1) is pre-treated, and the pre-treatment conditions are: acetone, 3 mol L -1 Hydrochloric acid, deionized water and ethanol were ultrasonically washed for 5 min respectively.
[0028] In the above technical solution, further, the constant current deposition condition in the step (1) electrodeposition is: the deposition current is 2 to 5 mA cm -2 ; Deposition time is 3600s~5400s; Deposition temperature is 60~90℃;
[0029] The constant current deposition conditions in the step (2) of electrodeposition are: deposition current 1-4 mA cm -2 ; Deposition time is 3600s~5400s; Deposition temperature is 20~30℃;
[0030] The constant current deposition conditions in the step (3) of electrodeposition are: deposition current 2-5 mA cm -2 ; The deposition time is 600s~1200s; The deposition temperature is 20~30℃.
[0031] In the above technical solution, further, in the step (1), the concentration ratio of the zinc salt precursor to the weak alkaline salt precursor is 1:1; the weak alkaline salt is hexamethylenetetramine; the concentration of the zinc salt precursor is 0.01-0.02 mol L -1 , preferably 0.01 to 0.015 mol L -1 ;
[0032] In the step (2), the concentration ratio of the cobalt salt precursor to the complexing agent is 1:1; the complexing agent is sodium citrate;
[0033] In the step (3), the molar ratio of the nickel salt precursor to the iron salt precursor is 1:1-3; the buffer is one or more of boric acid, sodium borate, and sodium citrate; the ligand is an ammonium salt, and the ammonium salt is preferably oxalammonium acid; in the electrodeposition solution III, the buffer concentration is 0.050-0.148 mol L -1 ; The concentration of the complexing agent is 0.0011~0.0037mol L -1 ; The concentration of the nickel salt precursor is 0.0004-0.0006 mol L -1 .
[0034] In the above technical solution, further, the concentration of the KOH solution in step (2) is 1 mol L -1 , soaking time 3 to 5 hours;
[0035] The washing conditions of step (1), step (2) and step (3) are washing with deionized water and ethanol in sequence until the pH is 7;
[0036] The drying in step (1), step (2) and step (3) is vacuum drying, the drying temperature is 50 to 100° C., and the drying time is 12 to 24 hours;
[0037] The stirring and dissolving time in step (1), step (2) and step (3) is 30 to 60 minutes.
[0038] The present invention also provides a self-supporting multi-layered nickel-iron double metal hydroxide nanosheet-coated cobalt hydroxide hollow nanorod array oxygen evolution electrode obtained by the above-mentioned continuous electrodeposition experiment, which can be used to catalyze the oxygen evolution reaction in the process of electrolysis of water to produce hydrogen under alkaline conditions; and can be applied to alkaline water electrolysis devices for renewable fuel cells, photoelectrocatalysis, alkaline anion exchange membrane water electrolysis, and electrolytic hydrogen generators.
[0039] The self-supporting electrode prepared by the method has good oxygen evolution electrocatalytic performance under alkaline conditions.
[0040] Compared with the prior art, the present invention has the following beneficial effects:
[0041] 1. The present invention adopts a three-time continuous electrodeposition method. The first electrodeposition method is to prepare a ZnO nanorod template; the second electrodeposition method is to prepare a cobalt hydroxide catalyst layer, and the ZnO template is easily removed in a KOH solution; the third electrodeposition method is to improve the catalytic activity and prepare a multi-layer nickel-iron double metal hydroxide-coated cobalt hydroxide catalyst layer. The present invention coats cobalt hydroxide hollow nanorods (one-dimensional structure) with nickel-iron double metal hydroxide nanosheets (two-dimensional structure) through three consecutive electrodeposition experiments under certain conditions, thereby obtaining a more dispersed oxygen evolution electrode with a unique three-dimensional layered hollow nanorod array composite structure, which has excellent oxygen evolution activity under alkaline conditions.
[0042] 2. A self-supporting nickel-iron double hydroxide-coated cobalt hydroxide hollow nanorod array electrode was obtained under mild conditions by continuous electrodeposition, and a unique morphology was obtained: the outer layer is composed of multiple layers of nickel-iron double hydroxide nanosheets, and the inner layer is composed of cobalt hydroxide hollow nanorods. The average diameter of each hollow nanorod is 0.2-1μm and the length is 2-3μm. The unique morphological structure of this electrode, the one-dimensional hollow nanotube (cobalt hydroxide) can disperse the two-dimensional nanosheet (nickel-iron double hydroxide nanosheet), ensures the looseness and stability of the nanostructure, and makes it have good catalytic activity and stability.
[0043] 3. Compared with powdered catalysts, the self-supporting multi-layered nickel-iron double metal hydroxide nanosheets coated with cobalt hydroxide hollow nanorod array oxygen evolution electrode prepared by this method has higher oxygen evolution catalytic activity, and the overpotential required for hydrogen production by electrolysis of water is smaller; the morphology is controllable. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 This is a SEM image of the self-supporting multi-layered nickel-iron double metal hydroxide nanosheet-coated cobalt hydroxide hollow nanorod array oxygen evolution electrode synthesized and prepared in Example 1.
[0045] Figure 2 The self-supporting multi-layered nickel-iron double metal hydroxide nanosheets coated with cobalt hydroxide hollow nanorod array oxygen evolution electrode obtained in the steps of Example 1 was tested for oxygen evolution in a three-electrode system at room temperature (25°C). -1 The polarization curve is obtained by linear voltammetric scanning using KOH solution as the electrolyte.
[0046] Figure 3 This is the SEM image of the self-supporting nickel-iron double hydroxide-coated cobalt hydroxide hollow nanorod oxygen evolution electrode according to the steps described in Example 2.
[0047] Figure 4The self-supporting nickel-iron double hydroxide-coated cobalt hydroxide hollow nanorod oxygen evolution electrode obtained in the steps of Example 2 was tested for oxygen evolution in a three-electrode system at room temperature (25°C). -1 The polarization curve was obtained by linear voltammetric scanning using KOH solution as the electrolyte.
[0048] Figure 5 The SEM image of the self-supporting oxygen evolution electrode of the self-supporting cobalt hydroxide hollow nanorod array obtained after implementing the steps described in Comparative Example 1.
[0049] Figure 6 To implement the self-supporting cobalt hydroxide hollow nanorod array oxygen evolution electrode obtained by the steps described in Comparative Example 1, an oxygen evolution test was carried out in a three-electrode system at room temperature (25° C.) with 1 mol L -1 The polarization curve was obtained by linear voltammetric scanning using KOH solution as the electrolyte.
[0050] Figure 7 This is a SEM image of the self-supporting layered nickel-iron double hydroxide nanosheet oxygen evolution electrode obtained after implementing the steps described in Comparative Example 2.
[0051] Figure 8 To implement the steps described in Comparative Example 2, the obtained self-supporting layered nickel-iron double metal hydroxide nanosheet oxygen evolution electrode was tested for oxygen evolution in a three-electrode system at room temperature (25°C). -1 The polarization curve was obtained by linear voltammetric scanning using KOH solution as the electrolyte.
[0052] Fig. 9 SEM image of the self-supporting ZnO nanorod template oxygen evolution electrode obtained by implementing the steps described in Comparative Example 3.
[0053] Fig.10 To implement the steps described in Comparative Example 3, the obtained ZnO nanorod template oxygen evolution electrode was tested for oxygen evolution performance in a three-electrode system at room temperature (25°C). -1 The polarization curve was obtained by linear voltammetric scanning using KOH solution as the electrolyte.
[0054] Fig.11 SEM image of the cobalt hydroxide hollow nanorod self-supporting oxygen evolution electrode obtained by implementing the steps described in Comparative Example 4. DETAILED DESCRIPTION
[0055] The preparation method, characteristics and applications of the self-supporting nickel-iron double hydroxide-coated cobalt hydroxide hollow nanorod array electrode are further described below in conjunction with the accompanying drawings, but the present invention is not limited in any way.
[0056] Example 1
[0057] The steps for preparing the hollow nanorod array oxygen evolution electrode are as follows:
[0058] (1) Electrodeposition reaction 1:
[0059] Preparation of electrodeposition precursor solution I: At room temperature, add 0.745 g (0.01 mol L -1 ) of Zn(NO3)2·6H2O was stirred in 250mL of deionized water at room temperature for 3min, and then 0.35g (0.01mol L -1 ) of hexamethylenetetramine and continue stirring to allow the solution to fully dissolve. During the stirring process, N2 is continuously introduced into the solution.
[0060] Electrodeposition experiment I: A three-electrode system was used, with a graphite plate as the counter electrode, a saturated calomel electrode as the reference electrode, and a nickel foam (2 × 2 cm, the nickel foam was cleaned with acetone, HCl, ethanol, and deionized water in advance) as the working electrode. The electrode was charged at 4 mA cm in a N2 atmosphere. -2 The constant current was 2000 s, the deposition time was 5400 s, the temperature of the electrodeposition precursor solution I was controlled at 80 °C, and after deposition, the obtained electrode was washed with deionized water until the pH was 7, and vacuum dried at 60 °C for 12 h to obtain a ZnO nanorod array self-supporting oxygen evolution electrode.
[0061] (2) Electrodeposition reaction 2:
[0062] Preparation of electrodeposition precursor solution II: At room temperature, weigh 0.351 g (0.005 mol L -1 ) of CoSO4·7H2O and 0.323 g (0.005 mol L -1 )C6H5Na3O7 was added into 250mL deionized water and stirred at room temperature to fully dissolve.
[0063] Electrodeposition experiment II: A three-electrode system was used, with a graphite plate as the counter electrode, a saturated calomel electrode as the reference electrode, and a ZnO nanorod array self-supporting oxygen evolution electrode (2×2 cm) obtained in the above experimental step (1) as the working electrode. The electrode was charged at 1 mA cm in a N2 atmosphere. -2 The current was constant, the deposition time was 3600s, the temperature of the electrodeposition precursor solution II was controlled at 30°C, and after deposition, the obtained electrode was washed with deionizer until the pH was 7. After vacuum drying at 60°C for 12h, the cobalt hydroxide-coated ZnO nanorod array self-supporting oxygen evolution electrode was obtained.
[0064] Removal of ZnO template: 1 mol L -1The sample was immersed in KOH solution for 3 h to remove the ZnO template, and then rinsed with deionized water and dried to obtain a cobalt hydroxide hollow nanorod array self-supporting oxygen evolution electrode.
[0065] (3) Electrodeposition reaction 3:
[0066] Preparation of electrodeposition precursor solution III: At room temperature, weigh 0.04 g (0.0005 mol L -1 ) of Ni(NO3)2·6H2O and 0.08g (0.0015mol L -1 ) of FeCl2·4H2O, 1.55 g (0.1 mol L -1 ) of H3BO3, 0.09 g (0.0025 mol L -1 ) of (NH4)2C2O4 was dissolved in 250 mL of deionized water, and N2 was continuously introduced into the solution during stirring.
[0067] Electrodeposition experiment III: A three-electrode system was used, with a graphite plate electrode as the counter electrode, a saturated calomel electrode as the reference electrode, and a cobalt hydroxide hollow nanorod array oxygen evolution electrode (2×2 cm) obtained in step (2) as the working electrode. A 5 mA cm -2 The current was constant, the deposition time was 600s, the temperature of the electrodeposition precursor solution III was controlled at 30°C, and after deposition, the obtained electrode was washed with deionizer until the pH was 7. After vacuum drying at 60°C for 12h, the self-supporting multi-layered nickel-iron double metal hydroxide nanosheets coated with cobalt hydroxide hollow nanorod array oxygen evolution electrode was obtained.
[0068] Depend on Figure 1 It can be seen that after continuous electrodeposition reaction, the morphological characteristics of the self-supporting nickel-iron double hydroxide nanosheet-coated cobalt hydroxide hollow nanorod array oxygen evolution electrode synthesized under relatively mild conditions are as follows: the outer layer is composed of multi-layered nickel-iron double hydroxide, and the inner layer is composed of cobalt hydroxide hollow nanorods. The final morphological characteristics are as follows: each multi-layered nanorod has an average diameter of 0.2-1 μm and a length of 2-3 μm.
[0069] Three-electrode test: Using a three-electrode system, oxygen is passed to a saturated concentration of 1 mol L -1 The polarization curve (such as Figure 2 The electrode prepared by this method has a -1 10 mA cm in KOH electrolyte solution -2The overpotential is 250 mV (without iR correction) at a current density of . The results show that the self-supporting multi-layered nickel-iron double hydroxide nanosheet-coated cobalt hydroxide hollow nanorod array oxygen evolution electrode prepared by this method has good oxygen evolution performance under alkaline conditions.
[0070] Example 2
[0071] Changing the preparation concentration of the ZnO template, the preparation method is as follows:
[0072] (1) Electrodeposition reaction 1:
[0073] Preparation of electrodeposition precursor solution I: At room temperature, add 1.49 g (0.02 mol L -1 ) of Zn(NO3)2·6H2O was stirred in 250mL of deionized water at room temperature for 3min, and then 0.7g (0.02mol L -1 ) of hexamethylenetetramine and continue stirring to allow the solution to fully dissolve. During the stirring process, N2 is continuously introduced into the solution.
[0074] Electrodeposition experiment I: A three-electrode system was used, with a graphite plate as the counter electrode, a saturated calomel electrode as the reference electrode, and a nickel foam (2 × 2 cm, the nickel foam was cleaned with acetone, HCl, ethanol, and deionized water in advance) as the working electrode. The electrode was charged at 4 mA cm in a N2 atmosphere. -2 The constant current was 2000 s, the deposition time was 5400 s, the temperature of the electrodeposition precursor solution I was controlled at 80 °C, and after deposition, the obtained electrode was washed with deionized water until the pH was 7, and vacuum dried at 60 °C for 12 h to obtain a ZnO nanorod array self-supporting oxygen evolution electrode.
[0075] (2) Electrodeposition reaction 2:
[0076] Preparation of electrodeposition precursor solution II: At room temperature, weigh 0.351 g (0.005 mol L -1 ) of CoSO4·7H2O and 0.323 g (0.005 mol L -1 )C6H5Na3O7 was added into 250mL deionized water and stirred at room temperature to fully dissolve.
[0077] Electrodeposition experiment II: A three-electrode system was used, with a graphite plate as the counter electrode, a saturated calomel electrode as the reference electrode, and a ZnO nanorod array self-supporting oxygen evolution electrode (2 × 2 cm) obtained in the above experimental step (1) as the working electrode. The electrode was charged at 1 mA cm in a N2 atmosphere. -2The current was constant, the deposition time was 3600s, the temperature of the electrodeposition precursor solution II was controlled at 30°C, and after deposition, the obtained electrode was washed with deionizer until the pH was 7. After vacuum drying at 60°C for 12h, the cobalt hydroxide-coated ZnO nanorod array self-supporting oxygen evolution electrode was obtained.
[0078] Removal of ZnO template: 1 mol L -1 The sample was immersed in KOH solution for 3 h to remove the ZnO template, and then rinsed with deionized water and dried to obtain a cobalt hydroxide hollow nanorod array self-supporting oxygen evolution electrode.
[0079] (3) Electrodeposition reaction 3:
[0080] Preparation of electrodeposition precursor solution III: At room temperature, weigh 0.04 g (0.0005 mol L -1 ) of Ni(NO3)2·6H2O and 0.08g (0.0015mol L -1 ) of FeCl2·4H2O, 1.55 g (0.1 mol L -1 ) of H3BO3, 0.09 g (0.0025 mol L -1 ) of (NH4)2C2O4 was dissolved in 250 mL of deionized water, and N2 was continuously introduced into the solution during stirring.
[0081] Electrodeposition experiment III: A three-electrode system was used, with a graphite plate electrode as the counter electrode, a saturated calomel electrode as the reference electrode, and a cobalt hydroxide hollow nanorod array oxygen evolution electrode (2×2 cm) obtained in step (2) as the working electrode. A 5 mA cm -2 The electrodeposition precursor solution III was kept at a constant current and a deposition time of 600 s. The temperature of the electrodeposition precursor solution III was controlled at 30° C. After deposition, the electrode was washed with deionized water until the pH value was 7. After vacuum drying at 60° C. for 12 h, the self-supporting nickel-iron double metal hydroxide nanosheet-coated cobalt hydroxide hollow nanorod array oxygen evolution electrode was obtained.
[0082] Depend on Figure 3 It can be seen that after continuous electrodeposition reaction, the morphological characteristics of the self-supporting nickel-iron double hydroxide-coated cobalt hydroxide hollow nanorod array oxygen evolution electrode synthesized under relatively mild conditions are as follows: the surface of each hollow nanotube has a disordered and rough structure, with an average diameter of 200-500nm and a length of 2-3μm.
[0083] Three-electrode test: A three-electrode system is used to pass oxygen to a saturated concentration of 1 mol L -1 The KOH solution was used as the electrolyte and the polarization curve (such as Figure 4 The electrode prepared by this method has a-1 10 mA cm in KOH electrolyte solution -2 At a current density of , the overpotential is 287 mV (without iR correction).
[0084] The performance is lower than that of the self-supporting multi-layered nickel-iron double metal hydroxide nanosheets coated with cobalt hydroxide hollow nanorod array oxygen evolution electrode obtained in Example 1. This is because the method changes the preparation concentration of the ZnO template, and after the electrodeposition reaction 2 and the electrodeposition reaction 3, the self-supporting nickel-iron double metal hydroxide coated with cobalt hydroxide hollow nanorod array oxygen evolution electrode ( Figure 3 The structure is disordered, rather than the nanosheets being interlaced and orderly coated on the surface of the cobalt hydroxide nanorods ( Figure 1 Therefore, the electrode has low catalytic activity in the alkaline oxygen evolution reaction.
[0085] Comparative Example 1
[0086] According to the steps described in Example 1, only electrodeposition reaction 1 and electrodeposition reaction 2 are carried out, and the specific method is as follows:
[0087] (1) Electrodeposition reaction 1:
[0088] Preparation of electrodeposition precursor solution I: At room temperature, add 0.745 g (0.01 mol L -1 ) of Zn(NO3)2·6H2O was stirred in 250mL of deionized water at room temperature for 3min, and then 0.35g (0.01mol L -1 ) of hexamethylenetetramine and continue stirring to allow the solution to fully dissolve. During the stirring process, N2 is continuously introduced into the solution.
[0089] Electrodeposition experiment I: A three-electrode system was used, with a graphite plate as the counter electrode, a saturated calomel electrode as the reference electrode, and a nickel foam (2 × 2 cm, the nickel foam was cleaned with acetone, HCl, ethanol, and deionized water in advance) as the working electrode. The electrode was charged at 4 mA cm in a N2 atmosphere. -2 The constant current was 2000 s, the deposition time was 5400 s, the temperature of the electrodeposition precursor solution I was controlled at 80 °C, and after deposition, the obtained electrode was washed with deionized water until the pH was 7, and vacuum dried at 60 °C for 12 h to obtain a ZnO nanorod array self-supporting oxygen evolution electrode.
[0090] (2) Electrodeposition reaction 2:
[0091] Preparation of electrodeposition precursor solution II: At room temperature, weigh 0.351 g (0.005 mol L -1 ) of CoSO4·7H2O and 0.323 g (0.005 mol L -1)C6H5Na3O7 was added into 250mL deionized water and stirred at room temperature to fully dissolve.
[0092] Electrodeposition experiment II: A three-electrode system was used, with a graphite plate as the counter electrode, a saturated calomel electrode as the reference electrode, and a ZnO nanorod array self-supporting oxygen evolution electrode (2 × 2 cm) obtained in the above experimental step (1) as the working electrode. The electrode was charged at 1 mA cm in a N2 atmosphere. -2 The current was constant, the deposition time was 3600s, the temperature of the electrodeposition precursor solution II was controlled at 30°C, and after deposition, the obtained electrode was washed with deionizer until the pH was 7. After vacuum drying at 60°C for 12h, the cobalt hydroxide-coated ZnO nanorod array self-supporting oxygen evolution electrode was obtained.
[0093] Removal of ZnO template: 1 mol L -1 The cobalt hydroxide hollow nanorod array self-supporting oxygen evolution electrode (such as Figure 5 ).
[0094] Three-electrode test: At room temperature, a three-electrode system was used to pass oxygen to a saturated concentration of 1 mol L -1 The polarization curve (such as Figure 6 The self-supporting electrode prepared by this method has a -1 10 mA cm in KOH electrolyte solution -2 The potential at the electrolysis current density is 290 mV (without iR compensation). This performance is lower than that of the self-supporting multi-layered nickel-iron double metal hydroxide nanosheet-coated cobalt hydroxide hollow nanorod array oxygen evolution electrode obtained in Example 1, because the cobalt hydroxide hollow nanorod array is a one-dimensional structure and has a low catalytic activity in the alkaline oxygen evolution reaction.
[0095] Comparative Example 2
[0096] According to the steps described in Example 1, only the electrodeposition reaction 3 is carried out. The reaction method is the same as the electrodeposition reaction 3 in Example 1. The specific method is:
[0097] Preparation of electrodeposition precursor solution III: At room temperature, weigh 0.04 g (0.0005 mol L -1 ) of Ni(NO3)2·6H2O and 0.08g (0.0015mol L -1 ) of FeCl2·4H2O, 1.55 g (0.1 mol L -1 ) of H3BO3, 0.09 g (0.0025 mol L -1) of (NH4)2C2O4 was dissolved in 250 mL of deionized water, and N2 was continuously introduced into the solution during stirring.
[0098] Electrodeposition experiment III: A three-electrode system was used, with a graphite plate electrode as the counter electrode, a saturated calomel electrode as the reference electrode, and a cleaned nickel foam substrate (2×2 cm) as the working electrode. A 5 mA cm -2 The electrode was washed with deionized water until the pH value was 7 and then dried under vacuum at 60°C for 12 hours to obtain the self-supporting multi-layered nickel-iron double metal hydroxide oxygen evolution electrode (such as Figure 7 ).
[0099] Three-electrode test: A three-electrode system is used to pass oxygen to a saturated concentration of 1 mol L -1 The polarization curve (such as Figure 8 The self-supporting electrode prepared by this method has a -1 10mAcm in KOH electrolyte solution -2 The potential at the electrolysis current density is 270 mV (without iR correction). This performance is lower than that of the self-supporting multi-layered nickel-iron double metal hydroxide nanosheet oxygen evolution electrode obtained in Example 1. This is because the edges of the nickel-iron double metal hydroxide nanosheet oxygen evolution electrode are easily stacked, which will cover the catalytic active sites and thus show lower OER catalytic activity.
[0100] Comparative Example 3
[0101] According to the steps described in Example 1, only the electrodeposition reaction 1 is carried out. The reaction method is the same as the electrodeposition reaction 1 in Example 1. The specific method is:
[0102] Preparation of electrodeposition precursor solution I: At room temperature, add 0.745 g (0.01 mol L -1 ) of Zn(NO3)2·6H2O was stirred in 250mL of deionized water at room temperature for 3min, and then 0.35g (0.01mol L -1 ) of hexamethylenetetramine and continue stirring to allow the solution to fully dissolve. During the stirring process, N2 is continuously introduced into the solution.
[0103] Electrodeposition experiment I: With graphite plate as counter electrode, saturated calomel electrode as reference electrode, and nickel foam (2×2 cm, nickel foam was cleaned with acetone, HCl, ethanol, and deionized water in advance) as working electrode, 4 mA cm -2The constant current was 5400s, the deposition time was 5400s, the temperature of the electrodeposition precursor solution I was controlled at 80°C, and after deposition, the obtained electrode was washed with deionized water until the pH was 7, and vacuum dried at 60°C for 12h to obtain a ZnO nanorod array self-supporting oxygen evolution electrode (such as Fig. 9 ).
[0104] Three-electrode test: A three-electrode system is used to pass oxygen to a saturated concentration of 1 mol L -1 The polarization curves (such as Fig.10 The ZnO nanorod array self-supporting electrode prepared by this method has a -1 10mAcm in KOH electrolyte solution -2 The potential at the electrolysis current density is 332mV (without iR correction). The experimental results show that the oxygen evolution activity of ZnO nanorod array is poor.
[0105] Comparative Example 4
[0106] According to the steps described in Example 1, only the electrodeposition reaction 1 and the electrodeposition reaction 2 are carried out, and only the immersion time in the KOH solution during the removal of the ZnO template is changed. The specific method is:
[0107] (1) Electrodeposition reaction 1:
[0108] Preparation of electrodeposition precursor solution I: At room temperature, add 0.745 g (0.01 mol L -1 ) of Zn(NO3)2·6H2O was stirred in 250mL of deionized water at room temperature for 3min, and then 0.35g (0.01mol L -1 ) of hexamethylenetetramine and continue stirring to allow the solution to fully dissolve. During the stirring process, N2 is continuously introduced into the solution.
[0109] Electrodeposition experiment I: A three-electrode system was used, with a graphite plate as the counter electrode, a saturated calomel electrode as the reference electrode, and a nickel foam (2 × 2 cm, the nickel foam was cleaned with acetone, HCl, ethanol, and deionized water in advance) as the working electrode. The electrode was charged at 4 mA cm in a N2 atmosphere. -2 The constant current was 2000 s, the deposition time was 5400 s, the temperature of the electrodeposition precursor solution I was controlled at 80 °C, and after deposition, the obtained electrode was washed with deionized water until the pH was 7, and vacuum dried at 60 °C for 12 h to obtain a ZnO nanorod array self-supporting oxygen evolution electrode.
[0110] (2) Electrodeposition reaction 2:
[0111] Preparation of electrodeposition precursor solution II: At room temperature, weigh 0.351 g (0.005 mol L -1 ) of CoSO4·7H2O and 0.323 g (0.005 mol L -1 )C6H5Na3O7 was added into 250mL deionized water and stirred at room temperature to fully dissolve.
[0112] Electrodeposition experiment II: A three-electrode system was used, with a graphite plate as the counter electrode, a saturated calomel electrode as the reference electrode, and a ZnO nanorod array self-supporting oxygen evolution electrode (2 × 2 cm) obtained in the above experimental step (1) as the working electrode. The electrode was charged at 1 mA cm in a N2 atmosphere. -2 The current was constant, the deposition time was 3600s, the temperature of the electrodeposition precursor solution II was controlled at 30°C, and after deposition, the obtained electrode was washed with deionizer until the pH was 7. After vacuum drying at 60°C for 12h, the cobalt hydroxide-coated ZnO nanorod array self-supporting oxygen evolution electrode was obtained.
[0113] Removal of ZnO template: 1 mol L -1 The ZnO template was removed by soaking in KOH solution for 6 h, and then rinsed with deionized water and dried to obtain a cobalt hydroxide hollow nanorod self-supporting oxygen evolution electrode. Fig.11 It can be seen that if the KOH solution is immersed for too long, many cobalt hydroxide hollow nanorods on the nickel foam substrate will dissolve.
[0114] Through the above mentioned Figure 1 , Figure 3 , Figure 5 , Figure 7 , Fig. 9 and Fig.11 Analysis shows that the preparation method of the present application obtains nanorods with a hollow structure. The hollow structure is formed after the second electrodeposition reaction. After the third electrodeposition reaction, nanosheet layered materials grow on the surface. The nanosheet layers are interlaced and coated on the surface of the cobalt hydroxide hollow nanorods.
Claims
1. A three-dimensional self-supporting hollow nanorod array oxygen evolution electrode, characterized in that: The electrode is based on nickel foam, on which catalytically active components cobalt hydroxide and nickel-iron double hydroxide are loaded; a hollow nanorod structure grows vertically on the surface of the nickel foam substrate, the hollow nanorod structure comprising a hollow nanorod-shaped cobalt hydroxide layer located inside, and multiple layers of nickel-iron double hydroxide nanosheets wrapped on the surface of the hollow nanorod-shaped cobalt hydroxide layer; the hollow nanorod has a diameter of 0.2 to 1 μm and a length of 2 to 3 μm.
2. The electrode according to claim 1, characterized in that: The diameter of the hollow nanorod is 0.5-1 μm.
3. The electrode according to claim 1, characterized in that: The nickel content of the nickel-iron double metal hydroxide is 5-10wt%; the cobalt content of the cobalt hydroxide is 75-80wt%; the catalytic active component loading per unit area on the foam nickel substrate is 0.045-0.055g cm -2 ; The weight ratio of the multi-layered nickel-iron double metal hydroxide nanosheets and the cobalt hydroxide hollow nanorods is 0.995-1.005:3.995-4.
005.
4. A method for preparing the electrode according to any one of claims 1 to 3, characterized in that: The steps include: (1) Preparation of ZnO nanorod array self-supporting oxygen evolution electrode by electrodeposition: Preparation of electrodeposition precursor solution I: Dissolve the zinc salt precursor and the weak alkaline salt precursor in a certain amount of deionized water at room temperature, and stir them in a N2 atmosphere to fully dissolve them; Electrodeposition experiment I: A three-electrode system was used, with a graphite plate as the counter electrode, a saturated calomel electrode as the reference electrode, and nickel foam as the working electrode. Constant current deposition was performed in a N2 atmosphere. After deposition, the obtained electrode was washed with deionized water and dried to obtain a ZnO nanorod array self-supporting oxygen evolution electrode. (2) Preparation of cobalt hydroxide coated ZnO nanorod array self-supporting oxygen evolution electrode by electrodeposition: Preparation of electrodeposition precursor solution II: Dissolve the cobalt salt precursor and the complexing agent in deionized water at room temperature and stir to fully dissolve; Electrodeposition experiment II: A three-electrode system was used, with a graphite plate as the counter electrode, a saturated calomel electrode as the reference electrode, and the working electrode being the ZnO nanorod array self-supporting oxygen evolution electrode obtained in step (1) above. After deposition was performed using a constant current in a N2 atmosphere; Washing and drying to obtain the cobalt hydroxide coated ZnO nanorod array self-supporting oxygen evolution electrode; Soaking in KOH solution to remove the ZnO template, then washing with deionized water and drying to obtain a cobalt hydroxide-coated ZnO hollow nanorod array self-supporting oxygen evolution electrode; (3) Preparation of NiFe LDHs-coated cobalt hydroxide hollow nanorod array oxygen evolution electrode by electrodeposition: Preparation of electrodeposition precursor solution III: stirring and dissolving the nickel salt precursor, the iron salt precursor, the buffer and the complexing agent at room temperature; Electrodeposition experiment III: using a three-electrode system, with a graphite plate electrode as the counter electrode, a saturated calomel electrode as the reference electrode, and the cobalt hydroxide-coated ZnO nanorod array oxygen evolution electrode obtained in step (2) as the working electrode; after constant current deposition under N2 atmosphere, washing and drying; washing with deionized water and drying to obtain the self-supporting NiFe LDHs-coated cobalt hydroxide hollow nanorod array oxygen evolution electrode.
5. The preparation method according to claim 4, characterized in that: The nickel foam of step (1) is pre-treated under the following conditions: acetone, 3 mol L -1 Hydrochloric acid, deionized water and ethanol were ultrasonically washed for 5 min respectively.
6. The preparation method according to claim 4, characterized in that: The constant current deposition conditions in the step (1) of electrodeposition are: deposition current 2-5 mA cm -2 ; Deposition time is 3600s~5400s; Deposition temperature is 60~90℃; The constant current deposition conditions in the step (2) of electrodeposition are: deposition current 1-4 mA cm -2 ; Deposition time is 3600s~5400s; Deposition temperature is 20~30℃; The constant current deposition conditions in the step (3) of electrodeposition are: deposition current 2-5 mA cm -2 ; The deposition time is 600s~1200s; The deposition temperature is 20~30℃.
7. The preparation method according to claim 4, characterized in that: In the step (1), the concentration ratio of the zinc salt precursor to the weak alkaline salt precursor is 1:1; the weak alkaline salt is hexamethylenetetramine; the concentration of the zinc salt precursor is 0.01 to 0.02 mol L -1 , preferably 0.01 to 0.015 mol L -1 ; In the step (2), the concentration ratio of the cobalt salt precursor to the complexing agent is 1:1; the complexing agent is sodium citrate; In the step (3), the molar ratio of the nickel salt precursor to the iron salt precursor is 1:1-3; the buffer is one or more of boric acid, sodium borate, and sodium citrate; the ligand is an ammonium salt, and the ammonium salt is preferably oxalammonium acid; in the electrodeposition solution III, the buffer concentration is 0.050-0.148 mol L -1 ; The concentration of the complexing agent is 0.0011~0.0037mol L -1 ; The concentration of the nickel salt precursor is 0.0004-0.0006 mol L -1 .
8. The preparation method according to claim 4, characterized in that: The concentration of the KOH solution in step (2) is 1 mol L -1 , soaking time 3 to 5 hours; The washing conditions of step (1), step (2) and step (3) are washing with deionized water and ethanol in sequence until the pH is 7; The drying in step (1), step (2) and step (3) is vacuum drying, the drying temperature is 50 to 100° C., and the drying time is 12 to 24 hours; The stirring and dissolving time in step (1), step (2) and step (3) is 30 to 60 minutes.
9. The electrode according to any one of claims 1 to 3 is used to catalyze the oxygen evolution reaction in the process of producing hydrogen by electrolysis of water under alkaline conditions.
10. The electrode according to any one of claims 1 to 3 is used as an oxygen evolution catalyst in an alkaline water electrolysis device of a renewable fuel cell, photoelectrocatalysis, alkaline anion exchange membrane water electrolysis, and electrolytic hydrogen generator.
Citation Information
Patent Citations
Bi-functional oxygen catalyst for graphene / nickel iron type hydrotalcite as well as preparation method and application thereof
CN105618060A
One-step electro-synthesis method of iron-layered double hydroxide nanosheet array
CN106149025A
Cited By
Preparation method of particle-self-supporting coupling oxygen evolution electrode for electrooxidation induction material local phase change
CN121204721A
A method for preparing a particle-self-supporting coupled oxygen evolution electrode by local phase transition of an electro-oxidation inducing material
CN121204721B